Sport Pedagogy Approaches for Enhancing Motor Skills and Learning Motivation in Physical Education: A Systematic Literature Review - Nono Hardinoto; Amansyah Amansyah; Bessy Sitorus Pane; Muhammad Reza Destya (INSPIREE: Indonesian Sport Innovation Review, 2026)
Purpose: This systematic literature review aimed to critically examine and synthesize existing empirical evidence on sport pedagogy approaches and their effects on motor skill development and learning motivation in physical education (PE) settings across school-age and early post-secondary populations. Materials and Methods: A systematic search was conducted across ERIC, SPORTDiscus, Web of Science, and PubMed databases for peer-reviewed studies published between 2015 and 2024. Studies were eligible if they employed experimental or quasi-experimental designs, reported quantitative or mixed-methods outcomes, and examined at least one identifiable sport pedagogy model. The PRISMA 2020 guidelines directed the selection and reporting process. Quality appraisal used the PEDro scale and Mixed Methods Appraisal Tool (MMAT). A total of 63 studies meeting all inclusion criteria were retained. Results: The evidence strongly supports game-centred approaches (Teaching Games for Understanding, Sport Education Model), constraints-led and ecological dynamics frameworks, cooperative learning, and self-regulated learning strategies as effective means of improving both motor proficiency (effect sizes d = 0.41–0.92) and autonomous motivation (d = 0.48–0.89). Integrated models combining tactical, social, and self-determination theory-aligned elements demonstrated the most consistent outcomes across school levels and sport disciplines. Conclusions: Sport pedagogy models that balance motor skill acquisition with motivational climate creation are superior to traditional direct instruction in producing sustained learning outcomes. Practitioners, curriculum designers, and policy-makers should prioritise evidence-based, student-centred pedagogical models in physical education programming.